Teacher stress in social interactions in the light of polyvagal theory. An ambulatory assessment approach to teachers’ heart rate and heart rate variability - Kühne, Fabienne; Wettstein, Alexander; Jenni, Gabriel; Schneider, Ida; grosse Holtforth, Martin; La Marca, Roberto (Frontiers in Neuroscience, 2024)
BackgroundTeaching is a genuinely social and highly demanding task. Drawing on Porges’ phylogenetic polyvagal theory with three evolved systems and three associated behavioral responses (social engagement, mobilization, and immobilization), we investigated teachers’ heart rate and heart rate variability in social interactions using ambulatory assessments.MethodsWe continuously measured heart rate and heart rate variability of 42 apparently healthy teachers on a work and leisure day with ambulatory electrocardiogram. We videotaped four consecutive, same-day lectures of each teacher. We trained observers to code student aggression and frontal teaching behaviors in an event sampling procedure with the behavior observation system for analyzing aggressive behavior in school settings. Additionally, perceived teacher-student relationship, social support from other teachers / school management, occupational complaints, and vital exhaustion were assessed by teacher self-reports.ResultsTeachers showed an increased heart rate and a decreased heart rate variability on a workday compared to a leisure day, anticipatory stress before classes, as well as insufficient recovery during lunchtime. Observed student aggression and high proportion of frontal teaching were associated with lower heart rate variability, while better perceived teacher-student relationship was correlated with higher heart rate variability. Differently, teachers’ psychological strain and heart rate variability were unrelated to each other.ConclusionCorresponding to polyvagal theory, results suggest that successful social interactions are fundamental for teachers’ favorable cardiological reactions.